(3GdScGf hGdJfejI GdHTQjIs - (3YHO Gddg(B, (3YWhjs ((3HjQhJ(B:s (3OGQ GdfgVI GdYQHjI(B,s, 2004)
(3GdJfejI GdHTQjI GdeSJOGeI hGdCef GdHTQj, GdYhdeI hGdJfejI GdHTQjI, GdabQ hGdJfejI GdHTQjI, eUWdMGJ GdabQ hGdJbOe hGdJMceGJ, GdGbJUGO Gdcdj hGdabQ, GdabQ hGdJfejI GdHTQjI, GdbVGA Ydi GdabQ, GdGSJgdGc hGdJejI GdHTQjI, efXhQ GdGSJgdGc hGJLGgGJg hYdGbGJg HGdCef GdZPGFj hGdejGg hfZjQ GdefGN hGdJfhY GdGjOjhdhLj, GdGSJgdGc hGdJfejI GdHTQjI, GdBKGQ GdHTQjI GdeJQJHI Ydi GSJgdGc GdehGQO GdWHjYjI hGdYed Ydi ehGLgJgG, GdeCI hGdJfejI GdHTQjI, Jecjf GdeQCI P, GdeQCI hGdJfejI hGdJfejI GdHTQjI, YOe GdeSGhGI Hjf GdLfSjf aj GdMbhb hGdMeGjI, Mbhb GdGfSGf hGdJfejI GdHTQjI, GdfVGdGJ aj SHd MQjGJ GdGfSGf, Mbhb GdGfSGf hGdJfejI GdHTQjI GdOjebQGWjI Jcad GdMbhb GdJj Jecf GdfGS aj GdcaGM VO GdabQ, GdOjebQGWjI hGdJfejI GdHTQjI, GVaGA GdWGHY GdOjebQGWj Ydi GdCef ef CLd efY GdUQGYGJ hHfGA GdSdGe , SjGSGJ YGeI dJMbjb CgOGa GdJfejI GdHTQjI(B.s
(3GdeQGLY U(B.1079s
Keywords: (3GdJfejI GdHTQjIs; (3GdLZQGajI GdHTQjIs; (3LZQGajI GdScGfs